Elucidating the epigenetic roles of notch1 in regulating gata3 and C-MYC in peripheral t cell lymphomas - Al-Khreisat, Mutaz Jamal Abed (2024)
Peripheral T cell lymphomas (PTCLs) are aggressive haematological malignancies with limited treatment options and poor prognoses. This study explores the epigenetic regulation of key genes (NOTCH1, GATA3, and c-Myc) in PTCL to uncover therapeutic targets and enhance the understanding of disease pathogenesis. Epigenetic inhibitors, such as Trichostatin A (TSA), Panobinostat (PA), and 5-Azacytidine (5-AZA), and the proteasome inhibitor, Ixazomib (IXA), were examined on three PTCL cell lines (SU- DHL-1, Ki-JK, and DL-40). MTT assays determined cytotoxicity through the calculated half maximal inhibitory concentration (IC50) and the combination drug index (CBI). Flow cytometry were employed to analyse apoptosis and cell cycle dynamics. Quantitative real-time polymerase chain reaction (RT-qPCR) evaluated GATA3, c-Myc, NOTCH1, and HDAC1–11 expression levels in PTCL cell lines post-drug treatment. Two-dimensional gel electrophoresis (2-DGE) revealed proteome pattern alterations in treated PTCL cell lines. DNA methylation profiles were identified in PTCL cases from formalin-fixed paraffin embedded (FFPE) specimens and treated PTCL cell lines using methylation-specific PCR (MS-PCR). Immunohistochemistry (IHC) examined NOTCH1, GATA3, and c-Myc protein expression from the FFPE specimens. The inhibitors showed a favourable response and significant effect on cell cytotoxicity, with significantly higher cytotoxicity indicated by lower IC50 values in SU-DHL-1 and Ki- JK compared to DL-40, which exhibited lower drug cytotoxicity with higher IC50 values, except for PA treatment, which showed moderate cytotoxicity. A combination of PA and 5-AZA exhibited a synergistic effect across all cell lines. All inhibitors induced significant (p < 0.05) cell apoptosis after 48 hours of treatment, with varying cell cycle arrest at the G0/G1 or S phases across different PTCL subtypes. Gene expression analysis demonstrated consistent and significant downregulation of NOTCH1 (p < 0.05) in all treatments, suggesting it as a potential therapeutic target. c-Myc showed consistent downregulation (p < 0.05) except in a few treated SU-DHL-1. GATA3 was mostly upregulated, with exceptions in a few treatments in DL-40 and nearly all Ki-JK. HDACs expression displayed variable patterns, and proteome analysis indicated significant (p < 0.05) changes in protein expression patterns in treated PTCL cell lines. DNA methylation profile revealed partial methylation of GATA3 and NOTCH1 in treated and untreated PTCL cell lines, while c-Myc remained unmethylated. Analysis of PTCL cases (n = 42) showed distinct protein expression profiles across PTCL subtypes, offering potential avenues for targeted therapy. However, protein expressions were not statistically associated with sociodemographic features, and clinicopathological characteristics (p > 0.05). Methylation analysis of PTCL cases (n = 28) identified higher NOTCH1 methylation (14.3%) compared to other genes, suggesting NOTCH1's potential role in gene silencing through epigenetic modifications. This study provides insights into PTCL epigenetic regulation and potential therapeutic targets, particularly when a combination of PA and 5-AZA exhibited a synergistic effect across all cell lines, highlighting customised therapy approaches. In conclusion, NOTCH1 was found to have a significant effect on c-Myc and GATA3 in the epigenetic processes and disease progression of PTCL.